Uji Daya Terima Puding Kacang Merah Sebagai Alternatif Makanan Selingan Untuk Remaja Putri Anemia - Afiska, Widya; Rotua, Manuntun; Yulianto, Yulianto; Podojoyo, Podojoyo; Nabila, Yunaini (JGK: Jurnal Gizi dan Kesehatan, 2021)
Background : Anemia problems can occur due to the low consumption of dietary sources of iron. A snack that is usually consumed only looks at the taste without seeing the nutritional content contained therein. One of the preventive measures that can be given is to improve the quality of snack foods. Red bean have a high iron content where in 100 grams there is 10.3 mg of iron. The purpose : This study aims to determine the formulation, acceptability and content of macro nutrients (energy, protein, fat, carbohydrates) and micro (iron) red bean pudding. Method : This study used an experimental method using a non-factorial Completely Randomized Design (CRD), there were 3 repetitions. The Results : The research subjects were 25 panelists who were somewhat trained. The results of the acceptance test showed that the research panelists showed F1 was the most preferred formula by the panelists, namely by adding 75 grams of red beans with an energy nutritional content of 107.7 Kcal (per 100 grams), 2.32% protein, 0.46% fat, carbohydrates. 23.58%, and iron 1.33%. Conclusion: F1 is the chosen formula because it has good receptivity, also contains nutrients that can meet the needs of a snack so that it can be used as a snack for anemic teenage girls. Suggestion : Research can be continued with research on the effect of giving red bean pudding to increase hemoglobin levels of anemic adolescent girls.